ANALISIS PENDAPATAN DAN POLA KONSUMSI RUMAHTANGGA PETANI KELAPA DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Karolina, Anita; Bakce, Djaimi; Yusri, Jum’atri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aimed to analyze the structure of income, household consumption patterns coconut farmers and the factors that influenced in Mandah Indragiri Hilir Municipality. To answer this purpose it was used the analysis of the income structure and logistic regression methods. Based on the result of the analysis the biggest household income of farmers are donated from work income that sourced from coconut farming income. Household consumption patterns of coconut farmers showed that expenditures of food consumption is greater than consumption of the non food. This indicated that the households of coconut farmers in Mandah are not prosperous yet. The dominant factors that affected household are food consumption patterns coconut farmers and the length of the householder education. Thus, in order to improve the welfare of coconut farmers, it needs to be a concerted effort to increase the income of the household, particularly through the coconut farming activities. This can be done by implementing the Goverment’s policy of stable prices as well as the effort of controlling the price of inputs. Beside that, it needs to be an effort to increase farmers’ knowledge through training and coaching.   Keywords: Structure of Income, Consumption Patterns, Welfare